Why Ireland starved : a quantitative and analytical history of the Irish economy, 1800-1850 - Mokyr, Joel, 1946- (London ; New York : Routledge, Taylor & Francis Group, 2006)
Technical changes in the first half of the nineteenth century led to unprecedented economic growth and capital formation throughout Western Europe; and yet Ireland hardly participated in this process at all. While the Northern Atlantic Economy prospered, the Great Irish Famine of 1845–50 killed a million and a half people and caused hundreds of thousands to flee the country. Why the Irish economy failed to grow, and ‘why Ireland starved’ remains an unresolved riddle of economic history. Professor Mokyr maintains that the ‘Hungry Forties’ were caused by the overall underdevelopment of the economy during the decades which preceded the famine. In Why Ireland Starved he tests various hypotheses that have been put forward to account for this backwardness. He dismisses widespread arguments that Irish poverty can be explained in terms of over-population, an evil land system or malicious exploitation by the British. Instead, he argues that the causes have to be sought in the low productivity of labor and the insufficient formation of physical capital – results of the peculiar political and social structure of Ireland, continuous conflicts between landlords and tenants, and the rigidity of Irish economic institutions. Mokyr’s methodology is rigorous and quantitative, in the tradition of the New Economic History. It sets out to test hypotheses about the causal connections between economic and non-economic phenomena. Irish history is often heavily coloured by political convictions: of Dutch-Jewish origin, trained in Israel and working in the United States. Mokyr brings to this controversial field not only wide research experience but also impartiality and scientific objectivity.
Publikace představuje kvantitativně i analyticky pojatý výklad hospodářských dějin Irska v letech 1800–1850. Autor podrobně zkoumá příčiny a průběh Velkého irského hladomoru, analyzuje demografické změny, zemědělskou produkci, tržní struktury a dopady hospodářské politiky. Kniha propojuje ekonomické modely s historickými daty a nabízí komplexní interpretaci, proč irská ekonomika v uvedeném období selhala.
První vydání George Allen & Unwin: rok 1983
Routledge dotisk: rok 2006
První brožované vydání: rok 2010
Obsahuje bibliografii, bibliografické odkazy a rejstřík
Keywords: 19. století; 1800-1850; hospodářské dějiny; hospodářská politika; hladomor; Irsko; monografie; 19th century; economic history; economic policy; famines; Ireland; monographs